THE EFFECT OF THE PROJECT CITIZEN LEARNING MODEL AND CRITICAL THINKING SKILLS ON THE LEARNING OUTCOMES OF SIXTH-GRADE STUDENTS AT SDN PEGADUNGAN 03 MORNING SCHOOL - Lilis Suryatie; Nurrohmatul Amaliyah; Irdalisa Irdalisa (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2026)
This study was motivated by the low learning outcomes in Pancasila Education among sixth-grade students at SDN Pegadungan 03 Pagi. In the implementation of the Merdeka Curriculum, learning models that can improve critical thinking skills and active student participation are highly needed. The Project Citizen learning model was chosen because it emphasizes collaborative, investigative, and problem-solving activities based on public issues. This study aimed to determine the effect of the Project Citizen learning model and critical thinking skills on students’ learning outcomes. The study employed a quantitative method with a 2×2 factorial quasi-experimental design. The sample consisted of 62 sixth-grade students divided into an experimental class and a control class. The independent variables were the Project Citizen learning model (X1) and critical thinking skills (X2), while the dependent variable was students’ learning outcomes (Y). Data were collected through critical thinking skill questionnaires and learning outcome tests. The results showed that: (1) there was an effect of the Project Citizen learning model on learning outcomes with Fcount 13.79 > Ftable 4.08; (2) there was an effect of critical thinking skills on learning outcomes with Fcount 21.45 > Ftable 4.08; and (3) there was an interaction between the Project Citizen learning model and critical thinking skills on learning outcomes with Fcount 5.00 > Ftable 4.08. Therefore, the Project Citizen learning model was effective in improving the learning outcomes of sixth-grade students at SDN Pegadungan 03 Pagi.